Taxonomic and functional diversity of zooxanthellate corals and hydrocorals in Southwestern Atlantic reefs - Bleuel, Jessica; Waechter, Luiza; Bender, Mariana; Longo, Guilherme O. (Frontiers in Ecology and Evolution, 2024)
The Southwestern Atlantic (SWA) harbors a relatively species poor but highly endemic coral assemblage due to historical processes, environmental and ecological drivers. Despite its low to moderate cover, corals still have a disproportionate contribution to ecosystem function and stability in this region. In the context of global change, it is imperative to know corals’ diversity and biogeographic patterns, yet a comprehensive approach is still missing for SWA corals. We integrated occurrence data from 21 sites and nice functional traits across 20 coral (scleractinian and hydrozoan) species to explore the taxonomic and functional diversity of coral assemblages in the SWA (1°N-27°S). We identified eight regions based on coral species composition, and then described their functional diversity using four metrics: functional richness (FRic), functional dispersion (FDis), functional evenness (FEve), and functional originality (FOri). Our findings reveal a prevalent pattern of high functional redundancy across these wight regions (indicated by low functional originality), with species occupying the edges of the trait space (high functional evenness) and converging around few trait values (low functional dispersion). Taxonomic and functional diversity peak between latitudes 13°S-20°S, decreasing with increasing distance from this diversity center, known as the Abrolhos Bank that harbors a wider continental platform. Such patterns resulted in low taxonomic and functional beta diversity and increased nestedness among regions caused by dispersal barriers and environmental filtering. The Southernmost region (22°-27°S) has the lowest taxonomic and functional diversity and comprises only three species that share similar traits, with these corals being: hermaphrodites, brooders and depth-tolerant, and having a wide corallite. As this region might become critical for corals in a future tropicalization scenario, tropical corals that share similar traits to those of the southernmost region can be more likely to thrive. Knowledge on taxonomic and functional diversity patterns can offer critical information to conservation by helping prioritizing areas with higher diversity and species with traits that enhance survival under climate change.